Evaluation of reading skills and Specific Learning Disability symptoms in Attention Deficit Hyperactivity Disorder - Cihat Çelik; Gülsen Erden; Sevim Özmen; Selma Tural Hesapçıoğlu (Klinik Psikoloji Dergisi, 2018)
Intelligence tests, symptom screening tests and reading tests are widely used in the evaluation of children who are referred to the clinic with learning difficulties and attention problems. In this study, 48 children with attention-deficit hyperactivity disorder diagnosed with such complaints were evaluated. The reading abilities of the children were assessed with Oral Reading Skills and Reading Comprehension Test (ORCT), learning disability symptoms were assessed with Specific Learning Disability Symptom Checklist (SLDSC) and intelligence scores were assessed with Wechsler Intelligence Scale for Children-IV (WISC-IV). Findings showed that the scores obtained from Parent and Teacher Forms of SLDSC were correlated with ORCT reading skills. Moreover, the WISC-IV verbal comprehension and full-scale IQ scores were significantly correlated with SLDSC scores. The research findings showed that ORCT and SLDSC would provide useful information in assessing the symptoms of clinical diagnostic groups.